Efficacy and safety of vericiguat in patients with HFrEF treated with sacubitril/valsartan: results from the VICTORIA trial. (14th October 2021) - Senni, M; Alemayehu, W; Sim, D; Edelmann, F; Butler, J; Ezekowitz, J.A; Hernandez, A.F; Lam, C.S.P; O'Connor, C.M; Pieske, B; Ponikowski, P; Roessig, L; et al.
Abstract: Background: In the VICTORIA trial (n=5050) the reduction in the primary composite endpoint of cardiovascular death (CVD) or heart failure hospitalization (HFH) was similar whether or not patients received sacubitril/valsartan. The distribution of those patients who received sacubitril/valsartan after randomization (drop-ins) and the relationship to the efficacy and safety of vericiguat is unknown. Purpose: We assessed the efficacy and safety of vericiguat in patients who were or were not treated with sacubitril/valsartan at baseline in the VICTORIA trial and the implications of post- randomization use of sacubitril/valsartan. Methods: A total of 5040 patients were analyzed according sacubitril/valsartan use at randomization or initiated after randomization. The efficacy of vericiguat on the primary composite endpoint and its components, time to first HF hospitalization or all-cause mortality, were assessed according to sacubitril/valsartan use. Safety outcomes included symptomatic hypotension, syncope, worsening renal function, and hyperkalemia. Results: Overall, 731 patients (360 on vericiguat and 371 on placebo) received sacubitril/valsartan at randomization. Patients treated with sacubitril/valsartan were twice as likely to be from Western Europe or North America, to have a lower ejection fraction and systolic and diastolic blood pressures, were more often on triple therapy (65.9 vs 58.6%), and more likely to have received biventricular pacing (17.9 vs 14.1%) or ICDs (42.3 vs 25.3%). For patients on sacubitril/valsartan at baseline, the adjusted hazard ratios for vericiguat's treatment effect on the primary composite outcome, CVD, and HFH was 0.94 (95% CI 0.74–1.20), 0.81 (95% CI 0.55–1.20) and 0.99 (95% CI 0.76–1.30), respectively. For those patients not on sacubitril/valsartan (2161 vericiguat; 2148 on placebo), the corresponding adjusted hazard ratios for vericiguat's treatment effect on the primary composite outcome, CVD, and HFH were 0.89 (0.80–0.98), 0.95 (0.82–1.11), and 0, 87 (0.78–0.98), respectively. There was no significant interaction on the treatment effect of vericiguat based on the use of sacubitril/valsartan. More placebo patients (n=238) received drop-in use of sacubitril/valsartan than vericiguat group (n=187; p=0.007) post-randomization during follow-up (Figure). Overall, adverse events in the 992 patients receiving sacubitril/valsartan (at either baseline or drop-in for at least 3 months) were not significantly different according to those on placebo vs vericiguat for symptomatic hypotension (21.0% vs 23.1), renal dysfunction (8.0 vs 9.0%), and hyperkalemia (10.3 vs 7.9%). Conclusions: Sacubitril/valsartan use was initiated more frequently after randomization in patients on placebo than on vericiguat. Concomitant use of sacubitril/valsartan did not alter the efficacy of vericiguat and was similarly tolerated in both study arms. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Merck & Co., Inc. and Bayer